Electrostatic origin of the unidirectionality of walking myosin V motors - Mukherjee, Shayantani (National Academy of Sciences, 2013)
Understanding the basis for the action of myosin motors and related molecular machines requires a quantitative energy-based description of the overall functional cycle. Previous theoretical attempts to do so have provided interesting insights on parts of the cycle but could not generate a structure-based free energy landscape for the complete cycle of myosin. In particular, a nonphenomenological structure/energy-based understanding of the unidirectional motion is still missing. Here we use a coarse-grained model of myosin V and generate a structure-based free energy surface of the largest conformational change, namely the transition from the post- to prepowerstroke movement. We also couple the observed energetics of ligand binding/hydrolysis and product release to that of the conformational surface and reproduce the energetics of the complete mechanochemical cycle. It is found that the release in electrostatic free energy upon changing the conformation of the lever arm and the convertor domain from its post- to prepowerstroke state provides the necessary energy to bias the system towards the unidirectional movement of myosin V on the actin filament. The free energy change of 11 kcal is also in the range of ∼2–3 pN, which is consistent with the experimentally observed stalling force required to stop the motor completely on its track. The conformational-chemical coupling generating a successful powerstroke cycle is believed to be conserved among most members of the myosin family, thus highlighting the importance of the previously unknown role of electrostatics free energy in guiding the functional cycle in other actin-based myosin motors.